A study to find optimal intra-cytoplasmic sperm injection timing of oocytes matured from germinal vesicle in in Vitro maturation cycles using a time lapse system - Anjana Ranganath; Lohith Chengappa Appaneravanda; Brigitte Gerstl; Nirmala Thondehal Math; Jyothi Menon; Devika Gunasheela (Wolters Kluwer Medknow Publications, 2021)
Background: The use of in vitro maturation (IVM) has allowed patients with polycystic ovary syndrome (PCOS) to have a positive fertility outcome, as it allows utilisation of immature oocytes to mature in vitro. Aim: The aim of the study is to establish an optimum intra-cytoplasmic sperm injection (ICSI) timing for IVM oocytes (germinal vesicles [GV] →, metaphase I [MI]→ and metaphase II [MII]) using time lapse system (TLS) for patients with PCOS. Setting and Design: Patients included in this study were diagnosed with PCOS, ≤35 years of age, anti-Müllerian hormone levels >6 ng/ml and antral follicle counts <40. Furthermore, we included only GV oocytes at the time of denudation in our study. Materials and Methods: Patients were minimally stimulated and their oocytes were retrieved. In vitro maturated oocytes were monitored using TLS to a maximum of 30 h. MII oocytes were further cultured and injected at five different time intervals (1-2 h, 3-4 h, 5-6 h, 7-8 h and >8 h) to observe for fertilisation, cleavage and utilisation rate. Statistical Analysis: Chi-square test was applied to compared the treatment groups Results: Amongst 328 oocytes retrieved from 27 female patients, 162 oocytes were in the time-monitored cohort and 162 oocytes were grouped as the control cohort. Maturation rate between GV→ MII was highest at 18 h in the time-monitored cohort MII (n = 57). Utilisation rate was highest when ICSI was performed between 5 and 6 h after the first polar body extrusion, n = 17 (63%). Conclusion: This study provides valuable insight into the optimal maturation timing using a TLS to yield the good number of oocytes. In addition, optimising ICSI timing is important to provide the best utilisation rate in an IVM cycle to achieve synchrony between nuclear and cytoplasmic maturation.